Maternal fatness and viability of preterm infants. Issue 6635 (28th May 1988) - Lucas, A; Morley, R; Cole, T J; Bamford, M F; Boon, A; Crowle, P; Dossetor, J F B; Pearse, R
Abstract : To investigate the effect of maternal fatness on the mortality of infants born preterm up to the corrected age of 18 months 795 mother-infant pairs were studied. Maternal fatness was defined by Quetelet's index (weight/(height 2 )) and all infants weighed less than 1850 g at birth. In 771 mother-infant pairs maternal age, complications of pregnancy, mode of delivery, parity, social class, and the baby's sex and gestation were analysed by a logistic regression model for associations with infant mortality (but deaths from severe congenital abnormalities and those occurring during the first 48 hours after birth were excluded). In a subgroup of 284 mother-infant pairs all infant deaths except those from severe congenital abnormalities were analysed in association with the infant's birth weight and gestation and the mother's height and weight; this second analysis included another 24 infants who had died within 48 hours after birth. In the first analysis mortality overall was 7% (55/771), rising from 4% (71/173) in thin mothers (Quetelet's index <20) to 15% (6/40) in mothers with grades II and III obesity (Quetelet's index >30). After adjusting for major demographic and antenatal factors, including serious complications of pregnancy, maternal fatness was second in importance only to length of gestation in predicting death of infants born preterm. In the second analysis mortality overall was 15% (44/284), rising from 9% (5/53) in thin mothers to 47% (8/17) in mothers with grades II and III obesity. In both analyses the relative risk of death by 18 months post-term was nearly four times greater in infants born to obese mothers than in those born to thin mothers. In addition, maternal fatness was associated with reduced birth weight, whereas it is associated with macrosomia in term infants. These data differ fundamentally from those reported in full term babies of obese mothers. It is speculated that the altered metabolic milieu in obesity may reduce the ability of the fetus to adapt to extrauterine life if it is born preterm.